2014
DOI: 10.1080/1550428x.2014.945676
|View full text |Cite
|
Sign up to set email alerts
|

Losing the Child They Thought They Had: Therapeutic Suggestions for an Ambiguous Loss Perspective with Parents of a Transgender Child

Abstract: In our culture, gender is a deeply felt, value-rich, organizing principle; it informs our understanding of who we are as an individual, as well as who we are supposed to be and how we are supposed to act within relationships. This is especially evident in family relationships, and perhaps most strongly in the relationships of mothers and fathers with their sons and daughters. Thus, when a person comes out as transgender or transsexual, parents often experience a profound sense of loss and confusion about their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 38 publications
3
48
0
12
Order By: Relevance
“…Previous studies have found that parents' reactions to gender variance represented a complicated amalgamation of rejection (Grossman et al, ), acceptance and support (Ryan et al, ; Simons et al, ), ambiguity (Wahlig, ), and family transitioning (Norwood, ). Parents' difficulties adjusting to gender variance and gender transition may create the potential for transgender youth to fear family rejection and negotiate feelings of uncertainty about the status of their family relationships (McGuire et al, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Previous studies have found that parents' reactions to gender variance represented a complicated amalgamation of rejection (Grossman et al, ), acceptance and support (Ryan et al, ; Simons et al, ), ambiguity (Wahlig, ), and family transitioning (Norwood, ). Parents' difficulties adjusting to gender variance and gender transition may create the potential for transgender youth to fear family rejection and negotiate feelings of uncertainty about the status of their family relationships (McGuire et al, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Other same-sex couples described family ambiguity due to shallow or limited support from family, support from select family members only, or support and incidents of rejection (Dziengel, 2012). Thus application of this theory is appropriate as SGM persons and their families often experience ambiguous loss and bound ary ambiguity over time (McGuire, Catalpa, Lacey, & Kuvalanka, 2016;Wahlig, 2014).…”
Section: Theoretical Foundation: Ambiguous Loss and Boundary Ambiguitymentioning
confidence: 99%
“…Le soutien familial est donc un des aspects les plus fondamentaux pour le bien-être des jeunes trans (McConnell, Birkett et Mustanski, 2016), mais il doit lui aussi être soutenu et accompagné. Le cheminement de tous les membres de la famille vers l'acceptation peut être difficile, prendre du temps, commencer par un sentiment de chocs et entraîner des conflits entre les parents comme au sein de la sphère familiale ; il implique souvent un processus d'adaptation (Pullen Sansfaçon et al, 2015) ou de deuil (Wahlig, 2015 Robichaud et Dumais-Michaud, 2015 ). Ainsi, décider d'autoriser son enfant à exprimer son identité de genre choisie à l'extérieur de la sphère familiale implique souvent une anxiété et un profond questionnement sur ce qui constitue la « bonne décision » (Pullen Sansfaçon et al, 2015).…”
Section: Prendre En Compte Le Contexte De Vie : Familles Et Modèles Punclassified